TINJAUAN YURIDIS TINDAK PIDANA MALPRAKTEK MELAHIRKAN YANG DILAKUKAN OLEH BIDAN (BERDASARKAN TINJAUAN KASUS PUTUSAN 963/PID.SUS/2013/PN.Rta) - Eka Lolita Eliyanti Pakpahan; Maitria Dwi Pradasel; Rosalia Gresella Br Malau; Samuel Brema Surbakti (STIH Awang Long Samarinda, 2021)
Provisions regarding the practice of health workers, both doctors and midwives, who commit criminal acts. Sometimes we hear of patients who have become disabled and even die after being treated by doctors or other health workers. Therefore, the community, especially those who are entangled in problems or whose families are affected by the case, can file a lawsuit such as in the Health Workforce Law regulations and the Midwifery Law provisions. Midwives must be trained and have experience in providing care in high risk situations. replied he did. So that a good work team must be concerned with women and their babies, and this can only be achieved by respecting each other's roles between the midwife and other team members involved in the process of caring for a mother and her baby. The method used in this research is Normative Juridical. The source of the data found was from existing sources, whether official, such as the applicable law and decisions. The results of this study were able to decide that someone who could be said to have committed childbirth malpractice behavior made by a midwife received a criminal incident listed in the Law No. must receive a fine in the case and be sentenced to prison.